Midnight crystal (New York Jove Books, 2010)
Adam White, the new head of the local Ghost Hunter Guild, enlists the aid of psychic private investigator and dreamlight reader Marlowe Jones to help him break a legendary curse and save the underworld.
"Jayne Ann Krentz writing as Jayne Castle"--Cover.
Keywords: Arcane Society (Imaginary organization) -- Fiction; Blessing and cursing -- Fiction; Psychic ability -- Fiction; Romantic suspense fiction